1991
DOI: 10.1086/185955
|View full text |Cite
|
Sign up to set email alerts
|

The postcollapse core of M15 imaged with the HST planetary camera

Abstract: We have obtained U-band images of the M15 core with the Planetary Camera of the Hubble Space Telescope. We are able to resolve stars down to the main-sequence turnoff (mu ~ 19.4) into the cluster center. We use crowded field photometry techniques to decompose M15 into bright resolved stars and a residual component consisting of stars at turnoff brightness or fainter. The residual component comprises 59% of the cluster light and follows a y =-0.71 power-law distribution for r > 1". The residual component flatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 17 publications
3
49
0
Order By: Relevance
“…High-resolution imaging of the centre of M15 has resolved the luminosity cusp into essentially three bright stars. Postrefurbishment HST star-count data confirm that the 2.2 ′′ core radius observed by Lauer et al (1991), and questioned by Yanny et al (1994), is observed neither by Guhathakurta et al (1996) with WFPC2 data nor by Sosin & King (1996) with FOC data. This surface-density profile clearly continues to climb steadily within 2 ′′ .…”
mentioning
confidence: 57%
“…High-resolution imaging of the centre of M15 has resolved the luminosity cusp into essentially three bright stars. Postrefurbishment HST star-count data confirm that the 2.2 ′′ core radius observed by Lauer et al (1991), and questioned by Yanny et al (1994), is observed neither by Guhathakurta et al (1996) with WFPC2 data nor by Sosin & King (1996) with FOC data. This surface-density profile clearly continues to climb steadily within 2 ′′ .…”
mentioning
confidence: 57%
“…The surface brightness distribution of M15 has been studied in detail by a number of authors ( Lauer et al 1991;Trager et al 1995;Guhathakurta et al 1996;Sosin & King 1997). Noyola & Gebhardt (2005) reanalyzed archival Wide Field Planetary Camera 2 ( WFPC2) images with a new technique that measures the integrated light to determine the surface brightness distribution in the dense central regions of the cluster.…”
Section: Surface Brightness Distributionmentioning
confidence: 99%
“… Our summed HRC‐I image of the centre of M15, showing the two bright sources, AC211 and M15 X‐2, and the positions of seven of the eight known millisecond pulsars (from SIMBAD). The circle represents the location and extent of the cluster core (which has a radius of 2.2 arcsec, see Lauer et al 1991). …”
Section: Chandra Hrc Imagingmentioning
confidence: 99%